2013
DOI: 10.3109/0886022x.2013.789970
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Right Internal Jugular Vein and Carotid Artery at Ipsilateral Head Rotation

Abstract: Ultrasound-guided right internal jugular vein catheterization (RIJV) should be the first choice to decrease the catheterrelated complications in high-risk hemodialysis patients. For this procedure, clinicians should identify the optimum positions of the RIJV, including its lower overlap with the carotid artery (CA) and high cross-sectional area of the vein. The aim of this prospective randomized study to evaluate the effects of mild ipsilateral head rotation combined with Trendelenburg position on RIJV cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…SR30 to the contralateral side resulted in anterior venal shift [2,3,6,8,[11][12][13][14][15][16]. These studies have shown that the IJV is commonly positioned lateral or anterolateral to the CCA, and the incidence of overlap was reported to be between 6 and 95%, depending on the method of calculation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…SR30 to the contralateral side resulted in anterior venal shift [2,3,6,8,[11][12][13][14][15][16]. These studies have shown that the IJV is commonly positioned lateral or anterolateral to the CCA, and the incidence of overlap was reported to be between 6 and 95%, depending on the method of calculation.…”
Section: Discussionmentioning
confidence: 96%
“…Although there is a high success rate (95%) when these landmarks are used [3], unexpected positional or anatomic variations of the CCA could result in inadvertent puncture of the CCA; this occurs in 3 to 10.6% of cases [4,5]. CCA punctures may result from an increased degree of overlap between the IJV and the CCA, and previous studies have shown variation in this overlap [3,[6][7][8].…”
Section: Catheterization Of the Internal Jugular Vein (Ijv) Is Amentioning
confidence: 99%
“…A summary of findings from several studies is shown (Table III). The CT-based studies determined the maximal diameter while USG measured the anteroposterior, transverse, or lateral diameters [32,87,113]. The average diameter obtained from USG showed a smaller average than CT, which was likely related to compression of the IJV during the procedure.…”
Section: Diametermentioning
confidence: 99%
“…[2][3][4] In addition, the right IJV has a much wider diameter and runs more superficially than the left IJV, and anatomical variations of the left IJV may partly account for the difficulty in achieving successful cannulation of the left IJV in certain patients. 10 Hemodialysis patients generally have an increased risk of catheter complications because of impaired hemostasis secondary to platelet dysfunction and repeated catheterization of the IJVs with large-bore dialysis catheters. 11,12 Vascular perforation and rupture may complicate catheter insertion, especially in older patients with multiple vascular problems due to thrombotic complications and decreased elasticity of the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,29 When the head is rotated away from the midline, the IJV becomes more directly anterior to the CA, resulting in a greater overlap of the IJV and the CA. 10 Therefore, excessive left rotation should be avoided to minimize the risk of unintentional CA puncture during right IJV cannulation. In the present study, each patient's head was positioned with the head rotated left at [20][21][22][23][24][25][26][27][28][29][30] .…”
Section: 11mentioning
confidence: 99%